Tren Ijtihad Kontemporer - Supani, Supani (Al-Manahij: Jurnal Kajian Hukum Islam, 2007)
Problems related to Islamic law come in accordance with social changing. The problems sometimes are only in different forms. Yusuf Qardhawi’s theory about ijtihad related much in classifying those problems. For those problems that have ever been discussed, they need to be re-analyzed using tariqah al- tarjih to obtain the strongest argumentation. Meanwhile for the new problems, they might be discussed by ijtuhad insha’i.